A methodological proposal of the Sustainolive international research project to drive Mediterranean olive ecosystems toward sustainability - De Luca, Anna Irene; Iofrida, Nathalie; González de Molina, Manuel; Spada, Emanuele; Domouso, Pablo; Falcone, Giacomo; Gulisano, Giovanni; García Ruiz, Roberto (Frontiers in Sustainable Food Systems, 2023)
Mediterranean olive growing characterizes, identifies, and can sustain the socioeconomic viability of rural areas, not only through the production of primary products but also through the management of renewable natural resources, and the conservation of landscape and biodiversity. However, high levels of mechanization, monocultures, intensive farming techniques, and the use of synthetic pesticides and fertilizers are threatening the environment and affecting rural communities in turn. In the last years, the agroecological discourse emerged as a transdisciplinary science merging agronomy, ecology, and socioeconomic sciences with the purpose of responding to socioeconomic and environmental concerns, responding to the globalized industrial food processing and intensive agriculture. In this context, the research project Sustainolive, guided by an international consortium of stakeholders from academia and the productive sector, has the aim of promoting sustainability in the olive oil sector through the implementation and promotion of innovative and technological solutions based on agroecological concepts. Through an innovative, transdisciplinary, and multi-actor approach, Sustainolive combines different types of knowledge (e.g., scientific, empirical, and traditional), disciplines (ranging from engineering to the humanities), and methodological approaches (e.g., Life Cycle Sustainability Assessment, Social Agrarian Metabolism and multicriterial analysis tools) to provide practical solutions that address the complexity of the olive sector. The results from the application of this methodology are expected to highlight which agroecological practices are more environmentally, economically, and socially sustainable and uncover how Mediterranean societies use agrarian biophysical resources.